Mechanoenzymatic reactions with whole cell transaminases: shaken, not stirred. Issue 9 (25th April 2022) - Carter, Eve M.; Ambrose-Dempster, Esther; Ward, John M.; Sheppard, Tom D.; Hailes, Helen C.
Abstract : The use of mechanoenzymatic reaction conditions with whole cell transminases to produce a range of amines in high yields and stereoselectivities. Abstract : Mechanochemical reactions have emerged in recent years as a green synthetic method because reactions can be performed more rapidly and using less solvent than traditional synthetic approaches. To date, very few mechanoenzymatic reactions have been described. For the first time, transaminases, which are widely used for the amination of aldehydes and ketones, have been used here under mechanoenzymatic conditions to produce amines using significantly less aqueous medium than conventional biocatalytic reactions. The direct use of whole cells was also possible and shorter reaction times could be used to provide amines efficiently with high yields and stereoselectivities.